Impact of nanoparticle shape on aligned MHD free convection flow of hybrid nanofluid over a vertical plate / Nur Sabarina Hairunanuar - Hairunanuar, Nur Sabarina (2021)
Hybrid nanofluid has been known as having a better thermal property in enhancing the heat transfer rate among researchers. In this present study, the impact of nanoparticle shape on free convection flow of hybrid nanofluid with base fluid of water, Copper (Cu) and Aluminium oxide (Al2O3) as the nanoparticles that move through a static vertical plate was investigated and had been solved numerically using Fourth Order Runge Kutta Method via Maple software. The dimensionless ordinary differential equation was derived by reducing the dimensional partial differential equation with similarity transformations. The behaviour of hybrid nanofluid was examined by considering different values of governing parameters which are the shape factor, inclination angle of magnetic field, magnetic interaction, volume fraction of nanoparticles and Grashof number. The effect on velocity and temperature profiles were plotted and analysed, and the numerical value of skin friction and Nusselt number were presented in tabulated form. It was observed that nanoparticle shape factor has a significant impact on hybrid nanofluid. Blade shaped nanoparticle in Cu-Al2O3/Water hybrid nanofluid produced the maximum velocity and temperature compared to platelets, cylindrical and bricks. The spherical shaped of nanoparticle in Cu-Al2O3/Water hybrid nanofluid computed the lowest temperature and followed by Al2O3/Water nanofluid with spherical shaped nanoparticle. Furthermore, it was found that the skin friction and Nusselt number for Cu-Al2O3/Water hybrid nanofluid is increased whenever the varied value of governing parameter increased. From this study, it is portrayed that hybrid nanofluid and nanofluid is a good heat transfer and thermal conductivity but with a good selection of nanoparticle shape, an enhancement of hybrid nanofluid can be produced.